Strengthening of Parts of Special-purpose Products by Diffusion Metallization - Guseinov, A.G.; Nazarov, I.A.; Asadov, Sh.A. (Herald of Azerbaijan Engineering Academy, 2022)
In article considers the issues of increasing the longevity and durability of special products using diffusion metallization method. By applying a coating to the working surface of parts of special products with modern methods, their longevity and reliability are ensured, and at the same time, quality indicators are increased. It is known that special-purpose products are operated under extreme conditions, and therefore their details are exposed to various types of food, corrosion and impressing factors. For this reason, during the production of special products, it is advisable to apply coating resistant to wear and corrosion to their parts by diffusion metallization. As the object of study, steel samples of 50PA, 30XН2МФА, 38XH3MA, 30XНМФА, 38XH3MFA were selected, which were used in the manufacture of parts of special purpose products.